THE GENDER-SPECIFIC NOUNS DENOTING PROFESSION/ROLE: THE MACEDONIAN CASE - Janusheva, Violeta (LLT Journal: A Journal on Language and Language Teaching, 2023)
Resting only upon projects, manuals, reports, and recommendations, so far, the ongoing gender-neutral language debate has not attracted broader research attention in the Macedonian language. Therefore, this qualitative study aims to provide thorough information on the Macedonian gender-specific nouns denoting profession/role by analyzing their entries in the current online Macedonian Dictionary and some documents, using the general inductive approach. Indicating that the singular/plural masculine generic nouns designating profession/role in one of their meanings refer to both sexes, the research results underpin the consequences of this usage, revealing the natural/grammatical gender collision, which latently contributes to women’s invisibility in society in general. The findings further suggest that some feminine derivations, which still have not been widely embraced due to the traditional values, and which perhaps sound slightly strange and even a bit humorous, do not depreciate women, and their usage should be endorsed and strongly encouraged.